Very severe oligozoospermia with AZFc microdeletion patients may affect intracytoplasmic sperm injection clinical outcomes: A propensity score matching analysis - Huan Zhang; Huanzhu Li; Shujuan Ma; Shuoping Zhang; Wen Li; Yifan Gu; Erchen Zhang; Liang Hu (Reproductive Medicine and Biology, 2024)
Abstract Purpose To explore whether spermatozoa from AZFc microdeletion patients affect their outcomes of intracytoplasmic sperm injection (ICSI). Methods Eighty‐five patients with AZFc microdeletion were recruited. A control group of one hundred and forty patients with severe oligozoospermia but without AZF microdeletion was selected using propensity score matching analysis with a 1:2 nearest neighbor algorithm ratio. The ICSI outcomes of the two groups were compared. Results AZFc microdeletion had lower rates of normal fertilization (73% vs. 80%, p = 0.17) and high‐quality embryos (44% vs. 58%, p = 0.07) than the control group. There was no significant difference in the clinical pregnancy rate, miscarriage rate, and live birth rate between the two groups. When the sperm concentration was <1 million/mL, the AZFc microdeletion group exhibited lower rates of fertilization (71% vs. 80%, p = 0.03), high‐quality embryo (44% vs. 58%, p = 0.02), clinical pregnancy (57% vs. 76%, p = 0.02), and live birth (49% vs. 72%, p = 0.01) than the control group. However, if sperm concentration was ≥1 million/mL, no significant differences were found. Conclusion If the sperm concentration is <1 million/mL, AZFc microdeletion do have a detrimental effect on most outcomes of ICSI.